2005
DOI: 10.1021/jp044792l
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the SQM Force Field Method to the Vibrational Spectra of Sodium Acetate

Abstract: The applicability of the scaled quantum mechanical force field (SQM FF) method to the prediction of the vibrational spectra of a charged molecule has been studied by the example of the acetate ion (CH3CO2-) in sodium acetate for which an efficient empirical valence force field (SVFF) based on observed IR spectra of six isotopomers of sodium acetate is available in the literature. Standard SQM FF calculations done on a free acetate ion at the B3LYP/6-31G level failed to give an acceptable estimation of even the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
4
13
0
Order By: Relevance
“…The presence of solvent significantly modifies these frequency values. Keresztury et al 44 have obtained B3LYP theoretical frequencies of hydrated acetate using the SCRF model and the basis set 6-31+G**. These authors report values of 1622 and 1327 cm -1 respectively for the asymmetric and symmetric stretching modes of OCO for acetate in water.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of solvent significantly modifies these frequency values. Keresztury et al 44 have obtained B3LYP theoretical frequencies of hydrated acetate using the SCRF model and the basis set 6-31+G**. These authors report values of 1622 and 1327 cm -1 respectively for the asymmetric and symmetric stretching modes of OCO for acetate in water.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Keresztury et al have shown that SQMFF-type calculations on the acetate ion at the B3LYP/6-31G* level were unable to explain the frequency splitting between the ν a and ν s modes of the carboxylate group. Furthermore, these authors pointed out the necessity to introduce a Na + counterion as a bidentate complex or as a water complex to obtain adequate vibrational descriptions of the antisymmetric and symmetric C−O stretching modes.…”
Section: Resultsmentioning
confidence: 99%
“…Addition of diffuse functions to the basis sets has been shown to be essential for accurate analyses of compounds containing lone pairs or anions or when dealing with transition structures, but it produces only a few changes when applied to molecules such as sugars. 28 Recently, Keresztury et al 29 have shown that SQMFF-type calculations on the acetate ion at the B3LYP/6-31G* level were unable to explain the frequency splitting between the ν a and ν s modes of the carboxylate group. Furthermore, these authors pointed out the necessity to introduce a Na + counterion as a bidentate complex or as a water complex to obtain adequate vibrational descriptions of the antisymmetric and symmetric C-O stretching modes.…”
Section: Resultsmentioning
confidence: 99%
“…The solvation structures and anion-cation interactions of carboxylate salts have been extensively studied by steady-state infrared (IR) spectroscopy [2][3][4][5][6][7][8][9] and theoretical calculations based on density functional theory (DFT). [10][11][12][13] These studies suggest that the carboxylate anion forms hydrogen-bonded complexes with the solvent, although the static and dynamic hydrogen bonding interactions are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%